EFFECTS OF HUMAN COMPETENCIES IN THE ADOPTION OF E-COMMERCE STRATEGIES AMONG SMEs IN KENYA - Kiplangat, Bii John; Shisia, Adam; Asienga, Irene Cherotich (IJECM, 2015)
The paper presents findings of a study which sought to determine the effects of Human factors and competencies in the adoption of E-Commerce strategies among Small and Medium Enterprises (SMES) in Kericho - Kenya. Specifically, the discussion focuses on the effect of ICT competencies/knowledge among Managers and employees and their readiness to adopt and use E-Commerce strategies. Further the paper discusses how attitudes, prioritization, level of training and leadership behavior among owners and employees affect the adoption or use of ECommerce strategies. A sample of 229 respondents interviewed composed of owners, managers and supervisors of SMEs operating in Kericho County. The findings presented show that support from Senior management which is part of the Human resource competencies, influences the adoption of E-Commerce to a large extent. Allocation of funds by the SME leaders was noted to have a significant influence on the adoption of E-Commerce. The study recommends policy realignments by agencies both private and Government dealing with SME growth to help the SMES in the development of E-Commerce. Training for both the SME owners
Keywords: Kenya; Human Competencies; E-Commerce Adoption; Small and Medium Enterprises